2015
DOI: 10.1007/978-94-017-7215-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Mucins and Cytokeratins as Serum Tumor Markers in Breast Cancer

Abstract: Structural and functional characteristics of mucins and cytokeratins are shortly described. Thereafter, those commonly used in breast cancer as serum tumor markers are considered. First CA15.3, MCA, CA549, CA27.29 mucins and CYFRA21.1, TPA, TPS cytokeratins alone or in association have been examined in different stages and conditions. Then their usefulness in monitoring disease-free breast cancer patients is evaluated. The central role of the established cut-off and critical change, the "early" treatment of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…These proteins maintain the overall structural integrity of epithelial cells and play a crucial role in tissue differentiation and specialization. CK expression has therefore been used as a marker of tissue differentiation, for example, to assess tumor malignancy (Barak, Goike, Panaretakis, & Einarsson, ; Moll, ; Nicolini, Ferrari, & Rossi, ) and progenitor cell activation. Immunostaining using a pan‐CK antibody showed that CKs were prominently expressed in the Abx mouse liver but were not expressed in the control mouse liver (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins maintain the overall structural integrity of epithelial cells and play a crucial role in tissue differentiation and specialization. CK expression has therefore been used as a marker of tissue differentiation, for example, to assess tumor malignancy (Barak, Goike, Panaretakis, & Einarsson, ; Moll, ; Nicolini, Ferrari, & Rossi, ) and progenitor cell activation. Immunostaining using a pan‐CK antibody showed that CKs were prominently expressed in the Abx mouse liver but were not expressed in the control mouse liver (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that elevation of serum tumour markers occurs significantly in advance of diagnosis of BC recurrence using radiodiagnostic methods (15,16). This is why some authors recommend the use of a combination of several tumour markers, especially CEA, CA 15-3 and cytokeratins, to increase the sensitivity of relapse detection, namely every 3 months after surgery during the first 5 years and every 6 months thereafter (17,18). Guidelines of the European Group on Tumour Markers and the National Academy of Clinical Biochemistry recommend the use of tumour markers for the diagnosis of early disease recurrences (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are a family of high-molecular weight glycoproteins expressed/produced by epithelial cells (Nicolini, Ferrari, & Rossi, 2015). Members of this family are involved in breast cancer development and altered expression is associated with cancer progression (Nicolini et al, 2015).…”
Section: Approaches Used To Detect Metastatic Lesions (On a Clinicmentioning
confidence: 99%
“…Members of this family are involved in breast cancer development and altered expression is associated with cancer progression (Nicolini et al, 2015). Carbohydrate antigen 15.3 (CA15.3) is the most common member in this family and approved by FDA as a biomarker for breast cancer and some other malignancies such as ovarian cancer, endometrial carcinoma, and nonsmall-cell lung cancer (Molina et al, 2008; Moore et al, 2008; Nicolini et al, 2015). Geraghty et al demonstrated that the serum CA15.3 level was elevated in 50–80% of breast cancer patients with metastasis (Geraghty, Coveney, Sherry, O’Higgins, & Duffy, 1992).…”
Section: Approaches Used To Detect Metastatic Lesions (On a Clinicmentioning
confidence: 99%